Torch light in the city: Auto/Ethnographic Studies of Urban Kampung Community in Depok City, West Java - Hestu Prahara (Antropologi Indonesia, 2015)
This monograph elaborates the anthropological discussion of place attachment among the residents of urban kampung neighborhood in one of Jakarta’s peripheral cities, Kota Depok. Within the socio-economic transformation in the cities and also alteration of physical landscape, the local residents who live in kampung neighborhood experience the feeling of ‘uprootedness’ but at the same time create place attachment through the act of incorporation. In this regard, kampung as a socio-spatial entity is discerned as potentiality within perpetual urban transformation. In particular, this monograph looks at the ways in which the production of place attachment constitutes a process mediated by practices related to social memories, kinship and ritual. Ethnographic data that I present in this monograph are gained through my ethnographic fieldwork during September 2011—Oktober 2012 among kampung residents in Kampung Bojong Pondokcina, Depok City, West Java. Since I (as researcher) am also part of the community that I study in this research, this monograph can be regarded as auto-ethnographic study in which in some part I also integrate self-narratives that place myself within the social context that I study.